Multiple stakeholder views of pre-school child weight management practices: A mixed-methods study. (November 2019) - Bradbury, Daisy; Porcellato, Lorna; Timpson, Hannah; Turner, Gillian; Goodhew, Shirley; Young, Ruth; Isaac, Nabil; Watson, Paula M
Objective: With the increasing prevalence of unhealthy weight status in pre-school children, this study sought to understand pre-school child weight management practices in Blackburn with Darwen, UK, with a view to informing appropriate intervention strategies. Design: Mixed-methods study (semi-structured interviews, quantitative survey). Setting: Urban–rural borough with high ethnic diversity in the North West of England. Methods: Phase 1 involved 15 semi-structured interviews with public health/service managers, health professionals and children's centre staff to explore current pre-school weight management practices, challenges and perceived training needs. Phase 2 involved a quantitative survey of multi-disciplinary health professionals ( n = 30) who work with pre-school children. Data were analysed thematically and perceived challenges organised into individual, interpersonal and organisational levels of the socio-ecological model. Results: Current pre-school child weight management practices appeared to be inconsistent, and staff were unable to locate clear protocols or referral pathways. Challenges most commonly related to individual family factors (e.g. families not perceiving child's weight status to be a problem) and organisational factors (e.g. lack of time). Perceived training needs differed between professions and included body mass index calculation and interpretation, weight-related communication and pre-school nutrition/physical activity guidelines. Conclusion: Inconsistencies in practice and a lack of clear pathways limited pre-school child weight management practices in Blackburn with Darwen. Although many challenges were attributed as external to the individual, potential steps to help practitioners cope with these demands are outlined.